Employment: The right to freedom of thought, conscience, religion or belief of women at work (Free and equal series, 2024)
Women have the right to freedom of thought, conscience, religion or belief (FoRB), including in employment. In practice however, many women face a range of challenges related to their religion or belief. This threatens not only their right to FoRB, but also their effective participation in the labour market on an equal footing with men. This explainer offers OSCE participating States, businesspeople, unions, civil society organizations and religious or belief groups practical recommendations to ensure respect for, and protection of women’s right to FoRB in employment.